Upacara Sapu Leger Massal Di Kabupaten Tabanan (Persepektif Pendidikan Agama Hindu) - Ni Putu Ayu Desi Wulandari (Pramana: Jurnal Hasil Penelitian, 2021)
The implementation of the mass Sweep Leger ceremony in Tabanan Regency is due to the Sapuh Leger Ceremony as Pengruwat because traditionally the Sapuh Leger is a cultural relic of the life of the Hindu community in Bali, which is customary and considered sacred. The Sapuh Leger Ceremony as an Implementation of Hindu Beliefs because the Sapuh Leger Ceremony as a religious ritual functions in manusa yadnya, which is related to the birth of children, especially those that fall on the day or Wuku Wayang. Sapuh Leger Ceremony as Cultural Preservation and Sapuh Leger Ceremony as Social Criticism. The values of Hindu religious education at the mass Sweeping Leger ceremony at the Upakara Geria Agung Beng Pasraman in Beng Village include: Character Education Values which consist of religious attitudes, compassion, hard work, never give up and responsibility, Sradha teachings and values. Bhakti, the values of the teachings of Tri Kaya Parisudha, the educational values of Panca Sradha, and the values of the teachings of Catur Paramitha.